Synthesis of new 3-(2-mercapto-4-oxo-4H-quinazolin-3-yl)-benzenesulfonamides with strong inhibition properties against the tumor associated carbonic anhydrases IX and XII - Bozdag, Murat; Alafeefy, Ahmed Mahmoud; Altamimi, Abdul Malik; Carta, Fabrizio; Supuran, Claudiu T.; Vullo, Daniela (Elsevier Ltd, 2017)
We report a series of novel metanilamide-based derivatives 3a–q bearing the 2-mercapto-4-oxo-4H-quinazolin-3-yl moiety as tail. All compounds were synthesized by means of straightforward condensation procedures and were investigated in vitro for their inhibition potency against the human (h) carbonic anhydrase (CA; EC 4.2.1.1.1) isoforms I, II, IX and XII. Among all compounds tested the 6-iodo 3g and the 7-fluoro 3i derivatives were the most potent inhibitors against the tumor associated CA IX and XII isoform (KIs 1.5 and 2.7 nM respectively for the hCA IX and KIs 0.57 and 1.9 nM respectively for the hCA XII).